Pemanfaatan Sampah Plastik Menjadi Eco-brick sebagai Teknologi Tepat Guna di Desa Lembah Sari, Kecamatan Batu Layar, NTB - Hidayati, Nurul; Fitrayudha, Adryan; Zarkasi, Ahmad; Khalis Ilmi, Muhammad; Yustissiani, Erni; Rasikhun, Hady; Samengasbumi, Ringgi Puteri; Irawan, Feri; Amaelisa, Viara; Ekasapta, Febrian (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Lembah Sari Village is one of the villages located in Batu Layar sub-district, West Lombok Regency, West Nusa Tenggara. The village has an area of 500 hectares with a population of 3,161 people. Lembah Sari Village is surrounded by hills and lots of green land, making it a special attraction for visitors to the village. The large population in Lembah Sari Village has its own problems, namely the number of villagers who use plastic waste in their daily activities so that this becomes a problem that needs to be addressed. As a form of scientific service to the community, the teaching staff together with Civil Engineering students of Muhammadiyah Mataram University together provide assistance in utilizing plastic waste into eco-bricks which are appropriate technology. This eco-brick is made by utilizing plastic waste around the village and then utilized into a form of building material or other materials. This eco-brick can be one of the solutions to reduce plastic waste in Lembah Sari village and be utilized as a business for the Lembah Sari village community